Multistage Modulation Formation of Hydrophilic-Hydrophobic Boron Carbon Nitride Nanomaterials - Zhang, Haotian (Langmuir : the ACS journal of surfaces and colloids, 2023)
Boron carbon nitride (BCN) ternary compounds are attractive due to their wide applications in adsorption, catalysis, protective coatings, etc. A simple way is provided to synthesize BCN materials with multistage modulation of hydrophilic-hydrophobic properties. Hydrophilic BCN nanoparticles with a contact angle of 31° and nearly superhydrophobic BCN sheets with a contact angle of 145° are obtained. The participation of a CuO additive in the synthesis process has the role of tuning morphologies, components, and properties of BCN materials. The addition of CuO would improve the hydrophobicity of BCN due to its microstructure with enhanced surface roughness. The interaction between melamine and boric acid on the surface of CuO(111) is investigated by first-principles calculations based on density functional theory (DFT). The tuned BCN materials have different photoelectric properties also, and their performance as photocatalysts has been verified in photocatalytic reactions for hydrogen from water. The achieved uniform hydrophilic BCN nanoparticles and hydrophobic BCN sheets have the potential for further practical applications